Gamification as a tool for increasing motivation in Uzbek EFL classrooms - Jurayeva Sarvinoz (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This conference thesis examines the role of gamification in increasing motivation among Uzbek learners in English as a foreign language (EFL) classrooms. Maintaining learners’ engagement and motivation remains one of the major challenges in language teaching. The study explores how game-based elements such as points, badges, competitions, quizzes, and rewards can create an interactive learning environment and encourage active participation. It also discusses the impact of gamification on learners’ motivation, classroom engagement, and language acquisition. The thesis highlights practical strategies for integrating gamified activities into English language teaching to improve learning outcomes.